2014
DOI: 10.1111/age.12225
|View full text |Cite
|
Sign up to set email alerts
|

Historical demographic profiles and genetic variation of the East African Butana and Kenana indigenous dairy zebu cattle

Abstract: Butana and Kenana breeds from Sudan are part of the East African zebu Bos indicus type of cattle. Unlike other indigenous zebu cattle in Africa, they are unique due to their reputation for high milk production and are regarded as dairy cattle, the only ones of their kind on the African continent. In this study, we sequenced the complete mitochondrial DNA (mtDNA) D-loop of 70 animals to understand the maternal genetic variation, demographic profiles and history of the two breeds in relation to the history of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 35 publications
1
23
1
Order By: Relevance
“…As expected for African cattle [ 7 ], haplogroup T1 (58.0%) is the most frequent. However, in contrast to virtually all African breeds from other areas where haplogroup T1 is essentially fixed [ 11 , 28 , 44 , 45 ], probably due to a number of sequential founder events that occurred as domesticated cattle spread from north to south across Africa [ 28 ], two other members of the macro-haplogroup T were also found in the Nile Delta breeds, both at rather high frequencies: T2 (19.4%) and T3 (16.1%). Whereas, haplogroup T5, which was previously reported at low frequencies both in Europe and Iraq [ 22 ], was not found in the Egyptian sample.…”
Section: Resultsmentioning
confidence: 99%
“…As expected for African cattle [ 7 ], haplogroup T1 (58.0%) is the most frequent. However, in contrast to virtually all African breeds from other areas where haplogroup T1 is essentially fixed [ 11 , 28 , 44 , 45 ], probably due to a number of sequential founder events that occurred as domesticated cattle spread from north to south across Africa [ 28 ], two other members of the macro-haplogroup T were also found in the Nile Delta breeds, both at rather high frequencies: T2 (19.4%) and T3 (16.1%). Whereas, haplogroup T5, which was previously reported at low frequencies both in Europe and Iraq [ 22 ], was not found in the Egyptian sample.…”
Section: Resultsmentioning
confidence: 99%
“…The demographic dynamics and history of Ethiopian goat populations were further investigated by generating Bayesian Skyline Plots (BSPs; Drummond, Rambaut, Shapiro, & Pybus, ) using the piecewise constant function implemented in BEAST 2.0 (Drummond, Suchard, Xie, & Rambaut, ) following Salim, Taha, Hanotte, and Mwacharo (). In brief, the HKY + G nucleotide substitution model was used for the analysis and each Markov Chain Monte Carlo simulation (MCMC) runs were performed for 20 million generations that were sampled every 1,000 generations.…”
Section: Methodsmentioning
confidence: 99%
“…No transversion mutation was observed on the d -loop region of mtDNA in Ethiopian cattle populations [ 11 ]. Whereas, 62 polymorphic sites (52 transitions, five transversions, five indels) were detected in the d -loop analysis of Kenana and Butan cattle populations in the neighboring Sudan [ 23 ]. In the current study, we observed 18 haplotypes (H = 18) which is lower than the haplotypes reported for Chinese cattle (H = 47) in same target region [ 21 ], however, higher than the haplotypes (H = 3) reported for Leiqiong cattle [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no (zero) percentage of variation was reported among Ethiopia cattle populations using the d -loop [ 11 ]. With same target region ( d -loop), only 2.4% of variation was observed between Kenana and Butan cattle in Sudan [ 23 ]. Very low percentage of variation was reported for North Ethiopian cattle based on the analysis of Y-chromosome simple sequence repeats (SSR) markers [ 7 ].…”
Section: Discussionmentioning
confidence: 99%